Persuasive Language Used in The Advertisements of Frankie Magazine - Darvolusius Nggara; I G. A. Sri Rwa Jayantini; Komang Dian Puspita Candra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2021)
This study discusses the persuasive language used in the advertisements of Frankie magazine. Persuasive language is a language used for when someone wants to influence others people to do or believe something. The aim of this study is focused to analyse the types of persuasive technique found in advertisement of Frankie magazine. The data of this study was analysed in descriptive qualitative method. This study applied the theory based on the Keraf (2007) to analysing the types of persuasive technique. There are seven types of persuasive technique by Keraf (2007) namely: rationalization, identification, suggestion, conformity, compensation, displacement and projection. The result of this study found three persuasive techniques from the six advertisements of Frankie magazine, those are compensation technique, suggestion technique, identification technique. The most dominant types of persuasive technique were found in advertisements of Frankie magazine, they are; suggestion is 3 (50%) data and identification is 2 (33.3%) data. The lowest dominant data of compensation technique is 1 (16.6%) data. The used types of persuasive technique in advertisements of Frankie magazine is one of the technique to help communicates the message and the content in the advertisements to the reader.